Synthesis and Biological Activity of Some 1-Isonicotinoyl- 3,5-Diphenyl-4-4Substituted Phenyl azo Pyrazoles - Dhingra, Vinod; Bhatwadekar, Renu; Pendse, Swati (Asian Journal of Chemistry, 2010)
1-Isonicotinoyl-3,5-diphenyl-4-substituted phenyl azo pyrazoles have been synthesised by the reaction of substituted phenyl azo dibenzoyl methane with the antitubercular drug isoniazid. These compounds were screened for antibacterial and fungicidal activities. Pyrazoles have shown 30–45% fungicidal effect and inhibitory effect to the extent of 25–35% has been noticed against E. coli, S. aureus and S. alvus.